The Effect of Online Pictures on English Proficiency and Classroom Interaction at Junior High School of Ban Kaengsriphoom Loei Thailand - Shinta Khusna Putri; Khoirul Anwar; Worachet Chanthai (DIDAKTIKA, 2023)
This study aims to determine the use of online pictures for English and interaction in class among junior high school students at Ban Kaengsriphoom School, Loei Thailand. This research uses ex-post facto, with a sample of 81 students who are a combination of grades VII, VIII and IX. Data collection was used on the results of student scores of the midterm and finalfinal exams test of semester one and questionnaires. Data analysis used pre-test and post-test scores (Paired Sample T-Test). The results of this study are: (1) there was an average increase in each group, for class VII (pre-test = 16.00 to post-test = 19.55), class VIII (pre-test = 16.24 to post-test = 23.20), class IX (pre-test = 14.71 to post-test = 19.19); (2) The average from the pre-test and post-test has a Sig. Value 0.000 is less than 0.05 (0.000 < 0.05); (3) The response from the questionnaire has an average of 4.64. It concludes that the online picture as an online media can increase student English proficiency because learning runs easily. So, students feel helpful to interact with teachers or other friends.